The application of BIM in the AECO industry - Li, Clyde Zhengdao; Zhen, Yu; Wu, Hengqin; Chen, Zhe; Xiao, Bing; Tam, Vivian W. Y. (Journal of Civil Engineering and Management, 2023)
Building information Modeling (BIM) has been applied to the whole life cycle planning of construction projects, becoming the latest “engineering brain”. Currently, researches on BIM involve various stages, but most of the review fields are relatively single and lack of systematic review and analysis. In order to comprehensively analyze the research trend of BIM in the field of engineering management, this paper takes the holistic analysis method as the framework. In the first stage, 2066 research projects were quantitatively analyzed by bibliometrics to clarify their research environment. In the second stage, scientometric analysis method is adopted to identify scholars, countries, key words and journal sources that have achieved fruitful results and influence in BIM research, and to clarify the research environment. In the last stage, indepth qualitative discussion is carried out to achieve three objectives: (1) to divide the whole life cycle of the article and summarize the research hotspots in each stage; (2) identify BIM application problems; (3) determine the future research direction. This work is helpful for researchers and practitioners in this field to quickly find influential and fruitful research or journals, and to understand the current research hot spots and trends for the next research planning.